2001
DOI: 10.1021/jp011078k
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Back-Electron Transfer Processes of Strongly Coupled Triphenyl Methane Dyes Adsorbed on TiO2 Nanoparticle Surface as Studied by Fast and Ultrafast Visible Spectroscopy

Abstract: Electron injection and back-electron transfer (BET) dynamics of triphenylmethane (TPM) dyes adsorbed on TiO 2 nanoparticles have been studied by fast and ultrafast pump-probe spectroscopy in the subpico-to microsecond time domain. TPM dyes form charge-transfer complex with TiO 2 nanoparticles as they get adsorbed on the surface. Among the three TPM dyes, pyrogallol red (PGR) and bromo-pyrogallol red (Br-PGR) have higher electronic coupling to or interaction with TiO 2 nanoparticles compared to aurin tricarboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(145 citation statements)
references
References 55 publications
5
140
0
Order By: Relevance
“…According to the equation E s à =sþ ¼ E s=sþ À E s , the oxidation potential of excited state phycocyanin is À1.41 vs SCE, where, E s/s+ is the oxidation potential of phycocyanin 0.53 V vs SCE, E s is the excited state energy 1.94 eV (excited state energy of the phycocyanin calculated [73] from the fluorescence maximum based on the reported method). The energy level of the conduction band of TiO 2 is À0.52 V vs SCE [74]. It suggests that the electron transfer from the excited state phycocyanin to the conduction band of TiO 2 is energetically favorable (Scheme 3).…”
Section: Fluorescence Quenching Characteristicsmentioning
confidence: 98%
“…According to the equation E s à =sþ ¼ E s=sþ À E s , the oxidation potential of excited state phycocyanin is À1.41 vs SCE, where, E s/s+ is the oxidation potential of phycocyanin 0.53 V vs SCE, E s is the excited state energy 1.94 eV (excited state energy of the phycocyanin calculated [73] from the fluorescence maximum based on the reported method). The energy level of the conduction band of TiO 2 is À0.52 V vs SCE [74]. It suggests that the electron transfer from the excited state phycocyanin to the conduction band of TiO 2 is energetically favorable (Scheme 3).…”
Section: Fluorescence Quenching Characteristicsmentioning
confidence: 98%
“…So, in principle it cannot fulfill the condition, which has been demonstrated by Lian and co-workers in ReCO complexes on TiO 2 film. On the other hand, in our earlier studies, we have observed single exponential electron injection time constant in many organic dye-nanoparticle systems, 6,7 where electron injection would only take place from the singlet excited state since the singlettriplet ISC takes long time (>1 ns). In such systems strong electronic coupling of the dye molecules with the nanoparticles would govern the electron-injection dynamics.…”
Section: Et Dynamics In Ru-cat/tio 2 Systemmentioning
confidence: 68%
“…The spectrum at each time delay consists of bleach in 470-500 nm wavelength region with a maximum at ≈480 nm, an absorption peak at ≈590 nm and another broad positive absorption band in the 700-1000 nm region which has been attributed to injected electrons in the conduction band. 6,7 The ab- sorption peak at 590 nm has been assigned to the Ru-cat cation radical. 11 Injection time in the present investigation has been determined by monitoring the appearance time of the signal of the injected electron.…”
Section: Et Dynamics In Ru-cat/tio 2 Systemmentioning
confidence: 99%
“…3. It was reported that TiO 2 NPs can form a strong CT complex with dye molecules, such as alizarin [25], triphenylmethane dyes [26], and Ru-Cat through the catechol spacer. It has already been discussed by Moser et al [27] that TiO 2 NPs can form a strong complex with catechols by formation of a five-membered ring.…”
Section: Resultsmentioning
confidence: 99%